REGULATORY CHARACTERISTICS OF THE STEP-DOWN SWITCHING REGULATOR WHICH CHARGES THE BATTERY FROM THE SOLAR BATTERY - V. Ya. Romashko (National Technical University "Kharkiv Polytechnic Institute", 2020)
Problem. An important element of autonomous power sources, built on the basis of solar batteries, is a battery, operating in a buffer mode. To extend the period of its use, it is necessary to ensure the appropriate modes of its charging and discharging, by regulating the charging and discharge currents. To ensure that maximum power can be transferred to the load in various operating modes, a matching switching regulator is included between the solar battery and the load. In the case of its application, it becomes possible to simultaneously regulate the charging current of the battery. For the most effective regulation of this current, it is necessary to know the regulatory characteristics of the regulator. Goal. The aim of the work is to determine and analyze the regulatory characteristics of the switching voltage regulator step-down type, which charges the battery from the solar battery. Methodology. Using the theory of switching voltage regulators, a relationship between the output characteristic of the source and the regulatory characteristic of the regulator are established. The graphs of the regulatory characteristics are carried out by the graphoanalytical method. Results. The dependence of the output current of the solar battery, from well as the current of the charged battery, on the relative time of the closed state of the key of the switching regulator are analyzes. A technique for constructing the regulatory characteristics of a switching regulator for a given type of output characteristic of a power source and operating voltage of a battery is proposed. For typical output characteristics of the solar battery, graphs of the regulatory characteristics of the switching regulator for various levels of illumination of the solar battery are constructed. When constructing the regulatory characteristics, the possibility of an intermittent current mode in the inductance of the switching regulator is taken into account. Originality. The results obtained make it possible to take into account the influence of the internal resistance of the power supply, in particular, substantially nonlinear, on the regulatory characteristics of the switching regulator. Practical value. The proposed technique can be used to determine the regulatory characteristics of other types of regulators, the power source of which has a non-linear output characteristic. Using the obtained regulatory characteristics, it is possible to determine the conditions under which maximum power will be transmitted from the solar battery to the battery. These characteristics can be used in the elaboration of solar battery charge controllers.